2011
DOI: 10.1523/jneurosci.4967-10.2011
|View full text |Cite
|
Sign up to set email alerts
|

Axon Regeneration Can Facilitate or Suppress Hindlimb Function after Olfactory Ensheathing Glia Transplantation

Abstract: Reports based primarily on anatomical evidence suggest that olfactory ensheathing glia (OEG) transplantation promotes axon regeneration across a complete spinal cord transection in adult rats. Based on functional, electrophysiological, and anatomical assessments, we found that OEG promoted axon regeneration across a complete spinal cord transection and that this regeneration altered motor responses over time. At 7 months after transection, 70% of OEG-treated rats showed motor-evoked potentials in hindlimb musc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
53
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(55 citation statements)
references
References 64 publications
2
53
0
Order By: Relevance
“…Retrograde targeting methods would be one means of achieving cell-specific neuronal growth factor expression (Fortun et al, 2009; Hollis et al, 2010), but the challenge of limiting growth factor expression to sub-regions of the dendritic tree would be substantially more difficult. Third, axonal regeneration may require interaction with specific rehabilitation strategies (García-Alías et al, 2009; Takeoka et al, 2011), approaches that will be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…Retrograde targeting methods would be one means of achieving cell-specific neuronal growth factor expression (Fortun et al, 2009; Hollis et al, 2010), but the challenge of limiting growth factor expression to sub-regions of the dendritic tree would be substantially more difficult. Third, axonal regeneration may require interaction with specific rehabilitation strategies (García-Alías et al, 2009; Takeoka et al, 2011), approaches that will be tested in future studies.…”
Section: Discussionmentioning
confidence: 99%
“…In humans, a phase I clinical trial of spinal cord injury repair demonstrated that transplantation of autologous OECs is feasible and safe [73,74]. In preclinical animal trials, it has been shown that transplanted OECs can survive and migrate within the injured spinal cord of rats [16,75], reduce scar and cavity formation [76,77], lead to improved functional locomotor and hindlimb recovery [78,79] and can restore breathing and climbing ability [80] even after complete transection of the spinal cord [79,81]. Similarly, Schwann cells have been shown to promote axon growth in spinal injury models [82] although they are not always as effective as OECs [83].…”
Section: Why Are Oecs Suitable For Neural Repair Therapies?mentioning
confidence: 99%
“…An exception may be the use of olfactory ensheathing cells (OECs), that surround the axons of the sensory neurons both in the olfactory epithelium and as they grow into the olfactory bulb. The OECs have been proposed to ameliorate function following spinal cord injury and nerve root avulsion in rodents [48][49][50][51]. In recent Phase I clinical trials, patients with spinal injury were transplanted with OEC grown from their nasal mucosa.…”
Section: Sources Of Somatic Stem Cells For Autologous Therapiesmentioning
confidence: 99%